Math, asked by adi866929, 10 months ago

find the value of k for which the pair of linear eqation have no solution 3x + y = 1 (2k - 1)x + (k-1)y = 2k+1

Answers

Answered by aleensethi04
1

Answer:

K - 2

Step-by-step explanation:

ANSWER

The given pair of equations are:

3x+y=1...(1)

(2k−1)x+(k−1)y=2k+1..(2)

Now rearranging eq1 and eq2 will get

3x+y−1=0...(3)

(2k−1)x+(k−1)y−(2k+1)=0..(4)

Now compare with

a  

1

​  

=3,b  

1

​  

=1,c  

1

​  

=−1

a  

2

​  

=2k−1,b  

2

​  

=k−1,c  

2

​  

=−(2k+1)

Now we get

a  

2

​  

 

a  

1

​  

 

​  

=  

2k−1

3

​  

,  

b  

2

​  

 

b  

1

​  

 

​  

=  

k−1

1

​  

,  

c  

2

​  

 

c  

1

​  

 

​  

=  

−(2k+1)

−1

​  

 

Now will take

a  

2

​  

 

a  

1

​  

 

​  

=  

b  

2

​  

 

b  

1

​  

 

​  

 

⇒  

2k−1

3

​  

=  

k−1

1

​  

 

⇒3k−3=2k−1

⇒3k−2k=−1+3

⇒k=2

Hence k=2 is the value

Answered by Priyanshulohani
0

\underline\mathfrak{Given:-}

\: \: \: \: \: \: \: {({2k} \: - \: {1})} \: x \: + \: {({k} \: - \: {2})} \: y \: \: = \: \: {5}

\: \: \: \: \: \: \: {({k} \: + \: {2})} \: x \: + \: y \: \: = \: \: {3}

\underline\mathfrak{To \: \: Find:-}

\: \: \: \: \: The \: \: value \: \: k \: ?

\underline\mathfrak{Solutions:-}

\: \: \: \: \: \fbox{\dfrac{a_1}{a_2} \: \: = \: \:  \dfrac{b_1}{b_2} \: \: \neq \: \: \dfrac{c_1}{c_2}}

\: \: \: \: \: \dfrac{{2k} \: - {1}}{{k} \: + \: {2}} \: \: = \: \:  \dfrac{{k} \: - \: {2}}{{1}} \: \: \neq \: \: \dfrac{5}{3}

\: \: \: \: \: \leadsto \dfrac{{2k} \: - {1}}{{k} \: + \: {2}} \: \: = \: \:  \dfrac{{k} \: - \: {2}}{{1}} \: \: \: \: \: .....{(1)}.

\: \: \: \: \: \leadsto \dfrac{{k} \: - \: {2}}{{1}} \: \: \neq \: \: \dfrac{5}{3} \: \: \: \: \: .....{(2)}.

\: \: \: \: \: Now, \: \: cross \: \: multiple \: \: in \: \: Eq. \: \: {(1)}.

\: \: \: \: \: \leadsto \dfrac{{2k} \: - {1}}{{k} \: + \: {2}} \: \: = \: \:  \dfrac{{k} \: - \: {2}}{{1}}

\: \: \: \: \: \leadsto {{2k} \: - {1}} \: \: = \: \: {({k} \: - \: {2})} \: \times \: {{({k} \: + \: {2})}}

\: \: \: \: \: \leadsto {{2k} \: - {1}} \: \: = \: \: {{k}^{2} \: - \: {2}^{2}} \: \: \: \: \: \: \: \: \: {[(a \: + \: b) \: (a \: - \: b) \: \: = \: \: ({a}^{2} \: - \: {b}^{2}]}

\: \: \: \: \: \leadsto {{2k} \: - {1}} \: \: = \: \: {{k}^{2} \: - \: {4}}

\: \: \: \: \: \leadsto {0} \: \: = \: \: {k}^{2} \: - \: {2k} \: - \: {4} \: + \: {1}

\: \: \: \: \: \leadsto {0} \: \: = \: \: {k}^{2} \: - \: {2k} \: - \: {3}

\: \: \: \: \: \leadsto {k}^{2} \: - \: {2k} \: - \: {3}

\: \: \: \: \: \leadsto {k} \: {({k} \: - \: {3})} \: + \: {1} \: {({k} \: - \: {3})}

\: \: \: \: \: \leadsto {({k} \: + \: {1})} \: \: \: {({k} \: - \: {3})}

\: \: \: \: \: \leadsto {k} \: \: = \: \: {-1} \: \: \: Or \: \: \: {k} \: \: = \: \: {3}

\: \: \: \: \: Hence, \: \: the \: \: the \: \: value \: \: of \: \: k \: \: is \: \:{-1} \: \: and \: \: {3}.

\: \: \: \: \:  \dfrac{{k} \: - \: {2}}{{1}} \: \: \neq \: \: \dfrac{5}{3} \: \: \: \: \: .....{(2)}.

__________________________________

Similar questions